Cognitive Challenges of Changeability: Multi‐Level Flexibility for Operating a Modular Chemical Plant1. Issue 11 (28th August 2017) - Müller, Romy; Urbas, Leon
Abstract: In changeable modular plants, the goal conflicts implied in adjusting the plant to current demands call for flexible strategy selection by operators on three levels: intervention, decision making, and cognitive meta‐control. The first level refers to making appropriate changes to the system. This requires flexibility on the second level. Flexibility in operators' choice of intervention and decision strategies depends on the third level, which enables a balance between stability and flexibility. The challenges resulting from these flexibility requirements are discussed by reviewing the literature on adaptive decision making and action control in volatile environments. Abstract : In changeable modular plants, flexible strategy selection by operators is required on multiple interacting levels. The cognitive challenges associated with this are discussed before the background of the empirical literature on adaptive decision making and action control in volatile environments.